1999
DOI: 10.1046/j.1365-2249.1999.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene expression in peripheral blood mononuclear cells (PBMC) from patients with pharmacologically treated cystic echinococcosis

Abstract: The influence of pharmacological treatment on the immune response of patients with Echinococcus granulosus infection was evaluated by reverse transcriptase-polymerase chain reaction (RT-PCR) to determine mRNA expression for IL-12 p35, IL-12 p40, interferon-gamma (IFN-gamma), tumour necrosis factor-alpha (TNF-alpha) and IL-4 in PBMC from 12 patients before and after chemotherapy and from seven uninfected controls. Most patients' PBMC showed measurable amounts of IL-12 p35, IL-4, IFN-gamma and TNF-alpha mRNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…In this way we directly evaluated the protein's action on cell motility, irrespective of its chemoattractant properties. The effects of AgB on circulating PMN from patients with CE might be interesting to evaluate, though we doubt whether the results would differ from those in cells from uninfected con- In previous in vitro and in vivo studies we found high Th1 cytokine concentrations (IFN-␥) in patients who responded to chemotherapy and high Th2 cytokine concentrations (IL-4 and IL-10) in patients who did not (32,33,34). If Th1 responses begin to damage the parasite, then it would be to the parasite's advantage to create a Th2 bias through the release of antigens that induce Th2-promoting cytokines, such as IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this way we directly evaluated the protein's action on cell motility, irrespective of its chemoattractant properties. The effects of AgB on circulating PMN from patients with CE might be interesting to evaluate, though we doubt whether the results would differ from those in cells from uninfected con- In previous in vitro and in vivo studies we found high Th1 cytokine concentrations (IFN-␥) in patients who responded to chemotherapy and high Th2 cytokine concentrations (IL-4 and IL-10) in patients who did not (32,33,34). If Th1 responses begin to damage the parasite, then it would be to the parasite's advantage to create a Th2 bias through the release of antigens that induce Th2-promoting cytokines, such as IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study investigating IL-12 gene expression in pharmacologically treated patients with CE, we suggested a role of this cytokine in resolving the disease, probably by promoting Th1 cell activation (IFN-␥) (34). In alveolar echinococcosis, in vivo treatment with recombinant IL-12 showed that this cytokine is of crucial importance in inhibiting larval growth (mainly through production of IFN-␥), suggesting its usefulness in therapy (17).…”
Section: ϫ2mentioning
confidence: 96%
See 1 more Smart Citation
“…Both in vitro and in vivo studies have shown that high levels of the Th1 cytokine IFN-γ were found in patients who responded to chemotherapy, whereas high levels of Th2 cytokines l (IL-4 and IL-10) occurred in patients who did not (Rigano et al, 1999b;Rigano et al, 1999a;Rigano et al, 1995b;Rigano et al, 1995a).…”
Section: T Cell Responses and Treatmentmentioning
confidence: 99%
“…In hydatid infections, both cell population profiles remain highly expressing, at least in cysts that survive the immune response. Elevated levels of IL-4, IL-5, IL-6, and IFN-␥ are produced in vitro by peripheral blood mononuclear cells (PBMC) isolated from infected human subjects and stimulated by HCF antigens (213)(214)(215)(216)(217)(218)(219). Elevated cytokine levels were also measurable in the sera from hydatid disease patients with lung and liver involvement (249).…”
Section: Established Cystsmentioning
confidence: 99%